Intercalation compounds of oxidized carbon black. Issue 107 (4th November 2016) - Maggio, Mario; Acocella, Maria Rosaria; Guerra, Gaetano
Abstract : Crystalline structure of oCB/2HT intercalate. In the top view, bases of hexagonal unit cells of graphite and of the hydrocarbon rotator order. Abstract : Oxidation studies on carbon black (CB) show that the degree of oxidation largely increases with initial BET surface areas. WAXD patterns suggest that oCB samples are mainly constituted by a disordered spatial arrangement of highly defective graphene oxide structural layers, with short in-plane correlation length (2–3 nm). This is confirmed by the ability of oCB to form ordered intercalation compounds, as for the first time reported here. In fact, tetraalkylammonium cations in which two of the alkyl groups possess long hydrocarbon tails (2HT) are able to induce formation of intercalate crystalline structures not only by ion exchange in ordered GO crystals but also by self-assembling with small and disordered oCB layers. WAXD patterns of oCB/2HT adducts show few 00 l reflections, indicating formation of an intercalate structure with a spacing between graphitic layers of 4.8 nm, as well as a diffraction peak at d = 0.42 nm, indicating the occurrence of a hexagonal rotator order of the intercalated hydrocarbon chains. The spacing between graphitic layers for oCB/2HT adducts (4.8 nm) is definitely higher than for the analogous GO/2HT adducts (3.4 nm) and corresponds to an orientation of the hydrocarbon tails nearly perpendicular to graphene planes.